KONTRIBUSI FAKTOR LINGKUNGAN FISIK DAN KIMIA KERJA TERHADAP PENCAPAIAN KINERJA KESEHATAN DAN KESELAMATAN KERJA PERUSAHAAN - Iwan Muhamad Ramdan (PROSIDING SEMINAR KIMIA, 2013)
Performance of Indonesian Occupational Health and Safety (OHS) with occupational accidents and occupational diseases as the main indicators has not been satisfactory. The main factors causing occupational accidents and occupation disease are human factors and environmental factors. Without prejudice to the human factors, the purposes of the study are to determine the relationship of physical and chemical environmental factors against the performance of OHS and its contribution to the performance of OHS. Analytical survey with cross sectional approach to Plywood Companies in East Kalimantan. Obtained a significant relationship between the physical and chemical environment variables with OHS performance (p = 0.043) and contribute 38.2% of the OHS performance.